London as a global financial center - Nagy, Andrea R., (SAGE Knowledge. Cases., 2007)
How, by 1900, had London become the world's pre-eminent commercial center? Over the centuries, England's capital city of London was transformed from a swampy area on the Thames, to a military headquarters for the Romans, to a chief settlement of the Saxons, to the political seat for the Normans, to a trading center during the middle ages, and finally to a financial and political capital that by the 19th century was the most powerful city in the world. As historian Jack Weatherford summarized it, "From the offices, conference halls, and trading rooms of the City flowed the money that kept Nelson's ships supplied at Trafalgar, financed the conquest of India, underwrote the mines of South America and the railroads of the world, supervised the banks of the largest and most far-flung empire in the world, and insured the legs of Hollywood movie stars." There are many factors that contributed to its success: geographical, political, economic, cultural, and institutional. Historians debate their relative importance, but it is clear that a number of elements linked together combined to produce a successful city. The crucial step in the city's development was its shift from trade to finance. "In the early years of the nineteenth century, the City of London began to be transformed from a bustling centre of tradesmen, small industries, shopkeepers and wealthy merchants, with a sizeable resident population, into a square mile of financial institutions and offices." Today London remains a nexus of the financial world. While many cities become trading centers, few become financial capitals. It is the development of London from trade to finance that is the focus of this case study.